Disrupted Working Memory Circuitry in Adolescent Psychosis - Eckfeld, Ariel; Karlsgodt, Katherine H.; Haut, Kristen M.; Bachman, Peter; Jalbrzikowski, Maria; Zinberg, Jamie; van Erp, Theo G. M.; Cannon, Tyrone D.; Bearden, Carrie E. (Frontiers in Human Neuroscience, 2017)
Individuals with schizophrenia (SZ) consistently show deficits in spatial working memory (WM), and associated atypical patterns of neural activity within key WM regions, including the dorsolateral prefrontal (dlPFC) and parietal cortices. However, little research has focused on adolescent psychosis (AP) and potential age-associated disruptions of WM circuitry that may occur in youth with this severe form of illness. Here we utilized each subject’s individual spatial WM capacity to investigate task-based neural dysfunction in 17 patients with AP (16.58±2.60 years old) as compared to 17 typically developing, demographically comparable adolescents (18.07±3.26 years old). AP patients showed lower behavioral performance at higher WM loads and lower overall WM capacity compared to healthy controls. Whole-brain activation analyses revealed greater bilateral precentral and right postcentral activity in controls relative to AP patients, when controlling for individual WM capacity. Seed-based psychophysiological interaction (PPI) analyses revealed significantly greater co-activation between the left dlPFC and left frontal pole in controls relative to AP patients. Significant group-by-age interactions were observed in both whole-brain and PPI analyses, with AP patients showing atypically greater neural activity and stronger coupling between WM task activated brain regions as a function of increasing age. Additionally, AP patients demonstrated positive relationships between right dlPFC neural activity and task performance, but unlike healthy controls, failed to show associations between neural activity and out-of-scanner neurocognitive performance. Collectively, these findings are consistent with atypical WM-related functioning and disrupted developmental processes in youth with adolescent psychosis.